Solid electrolyte, composite electrolyte and secondary battery

By introducing sulfonate and siloxane functional groups into the polymer electrolyte and adding fluorine atoms to the polyether chain to form a solid electrolyte membrane rich in lithium fluoride, the low conductivity and high voltage of the polymer solid electrolyte are solved. The problem of poor stability has significantly improved the rate performance and cycle stability of lithium metal batteries.

CN118919841BActive Publication Date: 2025-01-10SHENZHEN XINYUANBANG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411399138.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The existing polymer solid electrolytes have low conductivity and poor high voltage stability, which limits the practical application of lithium metal batteries.

Method used

Polymers based on structural formulas I and II are used as solid electrolytes, and the weak coordination interaction of lithium ions is adjusted by introducing sulfonate and siloxane functional groups, broadening the electrochemical window, and introducing fluorine atoms into the polyether chain to form poly Fluoroe, forming a weak solvated structure to improve conductivity and high voltage resistance.

Benefits of technology

It significantly improves the rate performance and cycle stability of the battery, reduces the interface impedance, and improves the ionic conductivity and high-temperature and normal temperature cycle capacity retention rate. The battery capacity retention rate is greater than 80% under 2C discharge conditions, and the capacity remains after 500 cycles. The rate reaches 70%-90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118919841B_ABST
    Figure CN118919841B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of secondary batteries, and in particular to a solid electrolyte, a composite electrolyte and a secondary battery. It comprises at least one of the polymers shown in structural formulas I and II; wherein R is selected from H, a C1-C3 alkyl group or a C1-C3 fluoroalkyl group; m is an integer of 1-1000, and n is an integer of 5-2000. The secondary battery based on the solid electrolyte provided by the present invention has high cycle stability and high energy density, and can inhibit the growth of lithium dendrites and the shuttling effect of polysulfides.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a solid electrolyte, a composite electrolyte and a secondary battery. Background Art

[0002] With the development of economy and technology, various products such as drones, electric vehicles, portable mobile devices (such as mobile phones and computers) are in urgent need of energy storage batteries with high energy density. The energy density of commercial lithium-ion batteries using graphite as the negative electrode material is close to the upper limit, but it still cannot meet the user's demand for energy density and range of the above equipment. Using lithium metal negative electrode materials with higher theoretical capacity to partially or completely replace the graphite negative electrode is an effective way to increase the energy density of the battery. However, lithium metal has a series of problems such as dendrite growth and uncontrollable side reactions during the charging and discharging process, which not only causes the battery capacity to decay too quickly, but also has the safety hazards of battery short circuit and battery fire and explosion.

[0003] In order to effectively improve the safety of lithium metal batteries, the use of inorganic ceramic solid electrolytes or polymer solid electrolytes avoids the hidden danger of flammable liquid electrolytes catching fire, which can greatly improve the safety of lithium metal batteries. In addition, the use of solid electrolytes can effectively reduce the weight of the battery and adapt to ternary positive electrodes with higher specific capacity and higher voltage, thereby greatly improving the energy density of the battery. However, there are huge problems with all-solid-state electrolytes in practical applications: First, the interface compatibility between inorganic ceramic solid electrolyte particles and positive and negative electrode materials is poor, which leads to a large electrochemical impedance of the whole battery, and the battery is difficult to operate stably at a high rate. Secondly, there are grain boundary problems inside the inorganic ceramic solid electrolyte particles, and the energy barrier between lithium ions crossing the grain boundaries is large, resulting in a low overall conductivity of the solid electrolyte. In addition, lithium dendrites are easy to grow between the grain boundaries of the solid electrolyte, resulting in battery failure. Therefore, the practical application of solid-state batteries must solve the interface compatibility problem and the grain boundary problem. Polymer solid electrolytes do not have grain boundary problems, and they also have excellent flexibility, good processability and rich designability, making them the focus of attention. However, the reported polymer electrolytes have a narrow electrochemical window and poor stability to high-voltage positive electrodes, which restricts their practical application. Therefore, the development of new conductive polymers that are stable to lithium metal and resistant to high voltage is particularly critical for the development of polymer solid-state batteries. Summary of the invention

[0004] The invention provides a solid electrolyte, a composite electrolyte and a secondary battery, which are used to solve the problems of low conductivity and poor high voltage stability of existing polymer solid electrolytes.

[0005] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a solid electrolyte, comprising at least one of the polymers shown in structural formulas Ⅰ and Ⅱ;

[0006]

[0007] Wherein, R is selected from H, C1-C3 alkyl or C1-C3 fluoroalkyl; m is an integer of 1-1000, and n is an integer of 5-2000.

[0008] Optionally, the polymer represented by structural formula I is selected from at least one of the following polymers:

[0009]

[0010] Wherein, m is an integer of 1-200, and n is an integer of 5-1000.

[0011] Preferably, the polymer represented by structural formula I is selected from at least one of the following polymers:

[0012]

[0013] Wherein, n is an integer from 5 to 1000.

[0014] Optionally, the polymer represented by structural formula II is selected from at least one of the following polymers:

[0015]

[0016] Wherein, m is an integer of 1-200, and n is an integer of 5-1000.

[0017] Preferably, the polymer represented by structural formula II is selected from at least one of the following polymers:

[0018]

[0019]

[0020] Wherein, n is an integer from 5 to 1000.

[0021] In a second aspect, the present invention provides a composite electrolyte comprising a liquid electrolyte and the solid electrolyte described above.

[0022] Optionally, based on the total mass of the composite electrolyte being 100%, the mass percentage of the solid electrolyte is 10%-90%.

[0023] Preferably, based on the total mass of the composite electrolyte being 100%, the mass percentage of the solid electrolyte is 60%-90%.

[0024] Optionally, the liquid electrolyte includes a solvent, a lithium salt and an additive, and the solvent is selected from at least one of ethylene carbonate, ethylene glycol dimethyl ether, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,3-dioxolane and propylene carbonate.

[0025] Optionally, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, and lithium perchlorate.

[0026] Optionally, the additive is selected from at least one of biphenyl, fluorobenzene, vinylene carbonate, trifluoromethyl vinyl carbonate, ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, vinyl sulfate, vinyl sulfite, methylene methane disulfonate, succinonitrile, adiponitrile, 1,2-bis(2-cyanoethoxy)ethane, and 1,3,6-hexanetrinitrile.

[0027] In a third aspect, the present invention provides a secondary battery, comprising a positive electrode, a negative electrode and the above-mentioned solid electrolyte or the above-mentioned composite electrolyte.

[0028] Optionally, the active material of the positive electrode is selected from at least one of lithium iron phosphate, lithium iron manganese phosphate, ternary nickel cobalt manganese, lithium-rich material, lithium cobalt oxide, and spinel lithium nickel manganese oxide.

[0029] Optionally, the active material of the negative electrode is selected from at least one of lithium metal, silicon, silicon oxygen, silicon carbon, liquid gold, and graphite.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention provides a polymer solid electrolyte based on polymers shown in structural formulas Ⅰ and Ⅱ, with polyether as the matrix structure, by introducing sulfonate and siloxane functional groups into the polyether main chain, respectively obtain polymers shown in structural formulas Ⅰ and Ⅱ, and use the weak coordination interaction of sulfonate and siloxane groups on lithium ions to adjust the polymer electrolyte solvation structure, on the one hand, broaden the electrolyte electrochemical window, and at the same time form a solid electrolyte membrane rich in lithium fluoride at the positive and negative electrode interfaces, so as to reduce the interface impedance of the whole battery, inhibit the growth of lithium dendrites, and improve the rate performance and long cycle stability of the battery. In addition, fluorine atoms are introduced into the polyether chain to form polyfluoroether, which can form a weak solvation structure in the electrolyte, improve the high voltage resistance of the electrolyte, and at the same time help to further improve its ionic conductivity and improve the interface contact of the electrolyte. The solid electrolyte of the present invention can be directly assembled with positive and negative electrodes into a secondary battery, and the obtained secondary battery has good rate performance and cycle stability. By mixing the solid electrolyte of the present invention with an existing liquid electrolyte to obtain a composite electrolyte, the performance of the battery can be further improved, the ion conductivity reaches 0.5-5mS / cm, the internal resistance growth rate is reduced to 5%-10%, the rate performance reaches a capacity retention rate of more than 80% under 2C discharge conditions, and the capacity retention rates after 500 cycles at high temperature and room temperature reach 70%-80% and 80%-90% respectively. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.

[0033] On the one hand, in some embodiments, the present invention provides a solid electrolyte, comprising at least one of the polymers shown in structural formulas I and II;

[0034]

[0035]

[0036] Wherein, R can be selected from H, C1-C3 alkyl or C1-C3 fluoroalkyl; m is an integer of 1-1000, and n is an integer of 5-2000.

[0037] In the polymers shown in structural formulas Ⅰ and Ⅱ, the R group forms a side chain of the polymer chain. When the R group is a fluoroalkyl group, it is beneficial to further improve the oxidation resistance potential of the electrolyte, and the ionic conductivity is reduced. When the R group is an alkyl chain, it can improve the flexibility of the polymer, thereby improving the conductivity of the polymer electrolyte. However, when the number of C atoms is greater than 3, the conductivity of the polymer is reduced due to the steric hindrance effect.

[0038] In some embodiments, the polymer represented by structural formula I is selected from at least one of the following polymers:

[0039]

[0040] Wherein, m is an integer of 1-200, and n is an integer of 5-1000.

[0041] In some preferred embodiments, the polymer represented by structural formula I is selected from at least one of the following polymers:

[0042]

[0043]

[0044] Wherein, n is an integer from 5 to 1000.

[0045] In some embodiments, the polymer represented by structural formula II is selected from at least one of the following polymers:

[0046]

[0047] Wherein, m is an integer of 1-200, and n is an integer of 5-1000.

[0048] In some preferred embodiments, the polymer represented by structural formula II is selected from at least one of the following polymers:

[0049]

[0050]

[0051] Wherein, n is an integer from 5 to 1000.

[0052] It should be noted that the polymers represented by structural formulas Ⅰ and Ⅱ in the present invention can be synthesized by conventional polymerization methods, and polymers with different structures and different polymerization degrees can be obtained by adjusting the selection and content of the polymerization monomers and the order of adding raw materials. The following lists a method for synthesizing the polymers represented by structural formulas Ⅰ and Ⅱ, respectively. It should be noted that the listed synthesis methods and specific parameters are not intended to limit the present invention.

[0053] The synthesis method of the polymer represented by structural formula I (m=0, R is H) is as follows: 0.5 mol of ethylene glycol and 0.5 mol of triethylamine are dissolved in 500 mL of N-methylpyrrolidone, 0.5 mol of thionyl chloride is added dropwise under ice bath conditions, and the mixture is stirred for reaction for 1 hour under ice bath conditions, warmed to room temperature, and stirred continuously for full reaction for 10 hours, and then washed three times with ultrapure water to dissolve the water-soluble salt, and the water and N-methylpyrrolidone are dried off in vacuum to obtain the polymer represented by structural formula I.

[0054] The synthesis method of the polymer represented by structural formula II (m=0, R is H) is as follows: 0.5 mol of ethylene glycol and 0.5 mol of triethylamine are dissolved in 500 mL of N-methylpyrrolidone, 0.5 mol of dimethyldichlorosilane is added dropwise under ice bath conditions, and the mixture is stirred for reaction for 1 hour under ice bath conditions, warmed to room temperature, and stirred continuously for sufficient reaction for 10 hours, and then washed three times with ultrapure water to dissolve the water-soluble salt, and the water and N-methylpyrrolidone are dried off in vacuum to obtain the polymer represented by structural formula II.

[0055] The solid electrolyte provided by the present invention is a polymer solid electrolyte based on the polymers shown in structural formulas Ⅰ and Ⅱ. The present invention uses polyether as the matrix structure, introduces sulfonate and siloxane functional groups into the polyether main chain, and obtains polymers shown in structural formulas Ⅰ and Ⅱ respectively. The weak coordination interaction of sulfonate and siloxane groups on lithium ions is used to adjust the polymer electrolyte solvation structure, on the one hand, to broaden the electrolyte electrochemical window, and at the same time, a solid electrolyte membrane rich in lithium fluoride is formed at the positive and negative electrode interfaces to reduce the interface impedance of the whole battery, inhibit the growth of lithium dendrites, and improve the rate performance and long cycle stability of the battery. In addition, fluorine atoms are introduced into the polyether chain to form polyfluoroether, which can form a weak solvation structure in the electrolyte, improve the high voltage resistance of the electrolyte, and at the same time, it is beneficial to further improve its ionic conductivity and improve the interface contact of the electrolyte.

[0056] Another embodiment of the present invention provides a composite electrolyte, comprising a liquid electrolyte and the solid electrolyte described above.

[0057] In some embodiments, based on the total mass of the composite electrolyte as 100%, the mass percentage of the solid electrolyte is 10%-90%, preferably 60%-90%. Specifically, as some embodiments of the present invention, the mass percentage of the solid electrolyte is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, and specific point values ​​between the point values. For the sake of space considerations, the present invention no longer exhaustively lists the specific point values ​​included in the range. In the composite electrolyte, the increase in polymer content can effectively improve the structural strength of the electrolyte membrane, inhibit the growth of lithium dendrites, and reduce the flammability of the electrolyte. However, too much polymer can also cause the electrolyte ion conductivity to drop significantly, thereby deteriorating the battery rate performance.

[0058] In some embodiments, the liquid electrolyte includes a solvent, a lithium salt and an additive, and the mass percentage of the liquid electrolyte is 10%-90%, preferably 20%-40%, based on the total mass of the composite electrolyte as 100%. Specifically, based on the total mass of the composite electrolyte as 100%, the mass percentage of the liquid electrolyte can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, and specific point values ​​between the point values. For space considerations, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0059] In some embodiments, the solvent is selected from at least one of ethylene carbonate (EC), ethylene glycol dimethyl ether (DME), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), 1,3-dioxolane (DOL), and propylene carbonate (PC). In some embodiments, based on the total mass of the liquid electrolyte as 100%, the mass percentage of the solvent is 50%-90%. Specifically, based on the total mass of the liquid electrolyte as 100%, the mass percentage of the solvent can be 50%, 53%, 55%, 58%, 60%, 62%, 65%, 66%, 70%, 74%, 75%, 79%, 80%, 82%, 85%, 88%, 90%, and specific point values ​​between the point values. For space considerations, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0060] In some embodiments, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, and lithium perchlorate. In some embodiments, in the liquid electrolyte, the concentration of the lithium salt is 0.1 mol / L-4 mol / L. Specifically, in the liquid electrolyte, the concentration of the lithium salt can be 0.1mol / L, 0.2mol / L, 0.4mol / L, 0.5mol / L, 0.55mol / L, 0.6mol / L, 0.65mol / L, 0.7mol / L, 0.8mol / L, 0.85mol / L, 0.9mol / L, 1.0mol / L, 1.2mol / L, 1.45mol / L, 1.5mol / L, 1.7mol / L, 2.0mol / L, 2.2mol / L, 2.5mol / L, 3.0mol / L, 3.3mol / L, 3.5mol / L, 3.88mol / L, 4.0mol / L, and specific point values ​​between the point values. For space considerations, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0061] In some embodiments, the additive is selected from at least one of biphenyl, fluorobenzene, vinyl carbonate, trifluoromethyl vinyl carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, vinyl sulfate, vinyl sulfite, methylene disulfonate, succinonitrile, adiponitrile, 1,2-bis(2-cyanoethoxy)ethane, and 1,3,6-hexane trinitrile. In some embodiments, based on the total mass of the liquid electrolyte as 100%, the mass percentage of the additive is 0.1%-3%. Specifically, based on the total mass of the liquid electrolyte as 100%, the mass percentage of the additive can be 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, and specific point values ​​between the point values. For space considerations, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0062] For a single polymer electrolyte, its ion conductivity is relatively low, and the cycle life of a high-load battery at room temperature under high rate conditions is relatively short. By combining the polymer electrolyte of the present application with a liquid electrolyte to form a composite electrolyte, it is possible to provide a higher ion conductivity, a wider electrochemical stability window, and good interface compatibility, thereby enabling the battery to cycle stably at room temperature, further improving the cycle life of the battery.

[0063] Another embodiment of the present invention provides a secondary battery, including a positive electrode, a negative electrode, and the solid electrolyte or the composite electrolyte.

[0064] In some embodiments, the secondary battery includes a solid-state battery and a semi-solid-state battery; the active material of the positive electrode is selected from at least one of lithium iron phosphate, lithium iron manganese phosphate, ternary nickel cobalt manganese, lithium-rich material, lithium cobalt oxide, and spinel lithium nickel manganese oxide; the active material of the negative electrode is selected from at least one of lithium metal, silicon, silicon oxygen, silicon carbon, liquid gold, and graphite.

[0065] In solid electrolytes, composite electrolytes and battery terminals, the polymers shown in structural formulas Ⅰ, Ⅱ and Ⅲ can effectively reduce the HOMO energy level of polymer molecules, thereby improving the oxidation resistance potential of ether polymer electrolytes. At the same time, siloxane groups, sulfonate groups and fluoroether groups can adjust the electrolyte solvation structure, which is conducive to the formation of an inorganic SEI / CEI film at the interface between the negative electrode and the high-voltage positive electrode, thereby improving the long-cycle stability of the battery.

[0066] The present invention is further described below by way of examples.

[0067] Table 1

[0068]

[0069] Note: The polymers 1-12 used in the following examples and comparative examples are selected from Table 1.

[0070] Example 1

[0071] The NCM811 was used as the positive electrode, the lithium sheet was used as the negative electrode, and the electrolytes in Table 2 were assembled in a CR2032 type button battery shell to obtain a secondary battery.

[0072] Example 2-Example 13, Example 28-Example 29 and Comparative Examples 1, 3, 5, 7

[0073] Examples 2 to 13, Examples 28 to 29 and Comparative Examples 1, 3, 5 and 7 include most of the operating steps in Example 1, except that:

[0074] The composition and content of the electrolyte, and the positive and negative electrode materials are shown in Example 2-Example 13, Example 28-Example 29 and Comparative Examples 1, 3, 5, and 7 in Table 2.

[0075] Embodiment 14

[0076] Ethylene carbonate was used as a solvent, lithium bis(fluorosulfonyl)imide was used as a lithium salt, and lithium difluorophosphate was used as an additive, and the mixture was uniformly mixed to obtain a liquid electrolyte, wherein the concentration of lithium bis(fluorosulfonyl)imide was 2.0 mol / L, and the mass ratio of ethylene carbonate to lithium difluorophosphate was 10:1. The obtained liquid electrolyte and solid electrolyte were uniformly mixed according to the ratio shown in Example 14 in Table 2 to obtain a composite electrolyte. NCM811 was used as a positive electrode, a lithium sheet was used as a negative electrode, and the composite electrolyte was assembled in a CR2032 button battery shell to obtain a secondary battery.

[0077] Examples 15-27, 30-43 and Comparative Examples 2, 4, 6, 8

[0078] Examples 15 to 27, Examples 30 to 43 and Comparative Examples 2, 4, 6 and 8 include most of the operating steps in Example 1, except that:

[0079] The composition and content of the composite electrolyte, and the positive and negative electrode materials are shown in Examples 15 to 27, Examples 30 to 43, and Comparative Examples 2, 4, 6, and 8 in Table 2.

[0080] Table 2

[0081]

[0082]

[0083] Performance Testing

[0084] The solid electrolytes / composite electrolytes of Examples 1 to 43 and Comparative Examples 1 to 8 were subjected to performance tests, and the test methods were as follows:

[0085] ①Ionic conductivity test:

[0086] Electrochemical impedance spectroscopy was performed using an electrochemical workstation. The ionic conductivity of the solid / composite electrolyte was calculated using the following formula:

[0087] σ=L / (RS)

[0088] Wherein, L is the thickness of the polymer solid / composite electrolyte, S is the area facing the stainless steel sheet, and R is the measured electrolyte bulk impedance.

[0089] ②Chemical window test:

[0090] The electrochemical window was measured by linear voltammetric scanning using an electrochemical workstation. The test conditions were: a starting potential of 4.0 V, a maximum potential of 6.5 V, and a scan rate of 5 mV / s.

[0091] The secondary batteries of Examples 1 to 36 and Comparative Examples 1 to 6 were subjected to performance tests, and the test methods were as follows:

[0092] ③Internal resistance test:

[0093] Under the condition of 0.5C rate, the battery cycle performance, rate performance and impedance before and after cycling were tested.

[0094] Internal resistance growth rate (%) = (impedance after cycle - impedance before cycle) / impedance before cycle × 100%

[0095] ④Rate performance test:

[0096] Take 3 batteries to be tested for capacity calibration; according to the actual capacity of the battery cell, perform rate performance test on the battery; the test method is to use 3C current for continuous discharge; before each discharge, use 1C constant current to charge to 4.3V, and then use 4.3V constant voltage to charge to 0.05C, the test temperature is 25℃, and the final measured capacity retention rate is the average value of the capacity retention rates of the 3 batteries to be tested.

[0097] ⑤45℃ high temperature cycle test:

[0098] The battery was placed under high temperature conditions of 45°C, charged at a constant current of 0.7C to 3.9V, then the constant voltage charging current was reduced to 0.02C, and then discharged at a constant current of 1C to 1.5V, and this cycle was repeated for 500 cycles;

[0099] The 500-cycle capacity retention rate was calculated as follows: discharge capacity at the 500th cycle / discharge capacity at the 1st cycle×100%.

[0100] ⑥25℃ normal temperature cycle test:

[0101] Place the battery at 25℃, charge it at 0.7C constant current to 3.9V, then charge it at 3.9V constant voltage, cut off current 0.05C, then discharge it at 1C constant current to 1.5V, repeat this cycle for 500 cycles;

[0102] The 500-cycle capacity retention rate was calculated as follows: the discharge capacity at the 500th cycle / the average discharge capacity at the 1st to 3rd cycle × 100%.

[0103] The test results are recorded in Table 3.

[0104] Table 3

[0105]

[0106]

[0107] From the data of Example 1-Example 43 and Comparative Example 1-Comparative Example 8, it can be seen that the present invention can directly use the polymer shown in structural formula I-II as a solid electrolyte, which can better improve the electrolyte electrochemical stability window and improve the rate performance and cycle performance of the secondary battery, and reduce the internal resistance growth rate of the secondary battery. In addition, by compounding the solid electrolyte containing the polymer shown in structural formula I-II with a liquid electrolyte, the ionic conductivity of the obtained composite electrolyte is significantly improved; the composite electrolyte is assembled into a secondary battery with the positive and negative electrodes, the internal resistance growth rate of the battery is reduced, and the rate performance is further improved. The present invention uses polyether as the matrix structure, introduces sulfonate, siloxane functional groups and fluorine substituents into the polyether chain, and uses the weak coordination interaction of sulfonate, siloxane and fluorine substituents on lithium ions to adjust the polymer electrolyte solvation structure, on the one hand, broaden the electrolyte electrochemical window, and at the same time form a solid electrolyte membrane rich in lithium fluoride at the interface of the positive and negative electrodes to reduce the interface impedance of the whole battery, inhibit the growth of lithium dendrites, and improve the rate performance and long cycle stability of the battery.

[0108] Comparison of Example 1-Example 10 and Comparative Examples 1, 3, 5, 7 and Example 14, Example 32-Example 40 and Comparative Examples 2, 4, 6, 8 shows that the structure of the polymer in the solid electrolyte affects the battery performance. The polymer side chains of Comparative Examples 1-Example 4 are C4. Due to the excessively long alkyl chain, the steric hindrance effect is too large, so the conductivity is reduced and the cycle performance is poor; Comparative Examples 5-6 use polyether polymers without sulfonate and siloxane functional groups as solid electrolytes, and their electrochemical stability windows are significantly narrower, mainly due to the poor oxidation resistance of the polymer chain; Comparative Examples 7-Example 8 are conventional EPO polymer electrolytes. Due to the solvation structure of separated ion pairs and the ether oxygen functional groups being easily oxidized, the electrolyte ion conductivity is low, the internal resistance growth rate of the manufactured battery is large, and the cycle performance is poor.

[0109] Comparing Examples 1 to 13 and Examples 32 to 43, it can be seen that the composition of the polymer in the solid electrolyte affects its performance. When the polymers shown in structural formulas I and II are used alone as electrolytes, compared with conventional polymer electrolytes, due to the special polymer structure design, the introduced sulfonate and siloxane functional groups can respectively adjust the solvation structure of the electrolyte by weak coordination, which is conducive to the formation of an inorganic SEI / CEI film at the interface between the negative electrode and the high-voltage positive electrode, thereby improving the long-cycle stability of the battery.

[0110] By comparing Examples 1-13 and 14-27, 32-43, it can be seen that when the solid electrolyte and liquid electrolyte containing the polymers shown in structural formulas Ⅰ and Ⅱ are used as composite electrolytes at the same time, the performance of the battery is more excellent; among them, the proportion of the solid electrolyte containing the polymers shown in structural formulas Ⅰ and Ⅱ will affect the performance of the battery, and its mass proportion needs to be at least 10%. The mass proportion of the solid electrolyte containing the polymer of the present invention in Examples 19, 23, and 27 is only 5%, the liquid electrolyte has a high proportion, the ion conductivity is high, but the battery capacity retention rate is low, which is mainly caused by excessive side reactions between the electrolyte and the electrode. The inventor further found that the content of the solid electrolyte containing the polymer shown in structural formulas Ⅰ-Ⅱ in the composite electrolyte is not the higher the better. When its mass proportion is 10%-60%, the optimal battery performance can be obtained at this time. When the polymers shown in structural formula I and structural formula II are used to form a solid electrolyte and are compounded with a liquid electrolyte, the composite electrolyte has a stronger effect on improving battery performance. This is because the composite electrolyte can take into account multiple properties such as high voltage, high ionic conductivity and interface stability.

[0111] From the comparison of Examples 28 to 31, it can be seen that the solid electrolyte and the composite electrolyte of the present invention are applicable to different positive and negative electrode systems, and the secondary batteries prepared have good cycle performance and rate performance.

[0112] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A solid electrolyte, characterized in that Including at least one of the polymers shown in structural formulas Ⅰ and Ⅱ; Wherein, R is selected from H, C1-C3 alkyl or C1-C3 fluoroalkyl; m is an integer of 1-1000, and n is an integer of 5-2000.

2. The solid electrolyte according to claim 1, characterized in that The polymer represented by the structural formula I is selected from at least one of the following polymers: Wherein, m is an integer of 1-200, and n is an integer of 5-1000.

3. The solid electrolyte according to claim 2, characterized in that The polymer represented by the structural formula I is selected from at least one of the following polymers: Wherein, n is an integer from 5 to 1000.

4. The solid electrolyte according to claim 1, characterized in that The polymer represented by structural formula II is selected from at least one of the following polymers: Wherein, m is an integer of 1-200, and n is an integer of 5-1000.

5. The solid electrolyte according to claim 4, characterized in that The polymer represented by structural formula II is selected from at least one of the following polymers: Wherein, n is an integer from 5 to 1000.

6. A composite electrolyte, characterized in that It comprises a liquid electrolyte and the solid electrolyte according to any one of claims 1 to 5.

7. The composite electrolyte according to claim 6, characterized in that Taking the total mass of the composite electrolyte as 100%, the mass percentage of the solid electrolyte is 10%-90%.

8. The composite electrolyte according to claim 7, characterized in that Taking the total mass of the composite electrolyte as 100%, the mass percentage of the solid electrolyte is 60%-90%.

9. The composite electrolyte according to claim 6, characterized in that The liquid electrolyte comprises a solvent, a lithium salt and an additive, wherein the solvent is selected from at least one of ethylene carbonate, ethylene glycol dimethyl ether, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,3-dioxolane and propylene carbonate; The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, and lithium perchlorate; The additive is selected from at least one of biphenyl, fluorobenzene, vinylene carbonate, trifluoromethyl vinyl carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, vinyl sulfate, vinyl sulfite, methylene methanedisulfonate, succinonitrile, adiponitrile, 1,2-bis(2-cyanoethoxy)ethane, and 1,3,6-hexanetrinitrile.

10. A secondary battery, characterized in that: It comprises a positive electrode, a negative electrode and a solid electrolyte as described in any one of claims 1 to 5 or a composite electrolyte as described in any one of claims 6 to 9.

Citation Information

Patent Citations

  • Synthetic method of 2-methoxy methylmesylate

    CN102875427A

  • Solid electrolyte containing polymer with main chain containing sulfur, solid secondary lithium battery formed by solid electrolyte as well as preparation method and application of solid electrolyte

    CN108232288A